Confident, positive, but interested? Exploring the role of teachers’ interest in their practice of differentiated instruction - Pozas, Marcela; Letzel, Verena; Bost, Nora; Reichertz, Julia (Frontiers in Education, 2022)
Given the substantial ongoing increase of individual learning demands, teachers are urged to address student heterogeneity in their daily teaching practice by means of differentiated instruction. As the successful and effective implementation of differentiated instruction relies mainly on teachers, research has intensively focused on examining teacher-related variables, such as teachers’ self-efficacy and attitudes, that have played a crucial role in their use of differentiated instructional practices. However, besides these well researched constructs, teacher interest is another important teacher-related variable that has, up to now, received very little attention and has been rarely incorporated into inclusive education research. Against this background, this study aimed to bring together previous research on teacher-related variables on their differentiated instructional practice, and extend prior literature by incorporate teachers’ interests. In total, 168 German in-service teachers from different school tracks participated in the study. Results from hierarchical linear regression analyses showed a significant and positive predicting role of teacher interests on their practice of differentiated instruction. Noteworthy is that teacher interests contributed significantly to their differentiated instructional practice, even after controlling for their self-efficacy and attitudes. Implications of the results, as well as further lines of research are discussed.